2014
DOI: 10.1016/j.appdev.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations among parental education, home environment quality, effortful control, and preacademic knowledge

Abstract: This study used a longitudinal design to examine whether effortful control mediated the associations of parental education and home environment quality with preacademic knowledge in toddlers and young preschoolers. The sample consisted of 226 children (2 to 4 years of age at T1) from socioeconomically disadvantaged backgrounds. Parents provided data on parent education and home environment quality. Children completed effortful control, early literacy, and early math assessments. T2 effortful control partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 78 publications
3
35
0
2
Order By: Relevance
“…In line with previous studies (e.g., Kochanska & Kim, 2014;Merz et al, 2014), self-regulated conduct was assessed at age 3. Given that toddlers are limited in their capacities to identify their thoughts and emotions, we used maternal reports and behavioural observation.…”
Section: The Current Studymentioning
confidence: 94%
“…In line with previous studies (e.g., Kochanska & Kim, 2014;Merz et al, 2014), self-regulated conduct was assessed at age 3. Given that toddlers are limited in their capacities to identify their thoughts and emotions, we used maternal reports and behavioural observation.…”
Section: The Current Studymentioning
confidence: 94%
“…The reason for averaging scores across assessments was to reduce the influence of measurement error. In the second study, Merz et al (2014) found that a broad composite measure of EF in a group of two- to four-year-old children predicted emergent mathematics and literacy a year later, even after controlling for initial performance in these domains. However, the mean assessment age in this study was three years.…”
Section: Introductionmentioning
confidence: 92%
“…Por sua vez, Duckworth e Seligman (2005), num estudo que envolvia alunos do 8º ano do ensino obrigatório nos EUA, verificaram que o autocontrolo avaliado por professores, por pais e pelos próprios alunos, era melhor preditor de vários aspetos do desempenho escolar (v.g., notas no fim do semestre, assiduidade às aulas ou pontuação em provas académicas) do que o próprio QI. Resultados que apontam no mesmo sentido têm sido, de resto, encontrados em estudos recentes que utilizam diferentes amostras e diferentes operacionalizações dos constructos de autocontrolo e de desempenho académico (Duckworth & Carlson, 2013;Merz et al, 2014;Véronneau, Hiatt-Racer, Fosco, & Dishion, 2014).…”
Section: Autocontrolo E Desempenho Académicounclassified